Study on the Influence and Mechanism of Resveratrol on Cognitive Impairment in Chronic Kidney Disease Rats Through Regulating Gut Microbiota and the TLR4/NFκB Pathway - Shao B; Nong Y; Lin Y; Meng Y; Zhou Y; Huang M; Huang F; Wang J (Journal of Inflammation Research)
Binbin Shao,1 Yanfei Nong,1 Yongshuang Lin,2 Yan Meng,1 Yi Zhou,1 Meiying Huang,3 Feifan Huang,3 Jie Wang3 1Graduate School, Youjiang Medical University for Nationalities, Baise, Guangxi, 533000, People’s Republic of China; 2The First Affiliated Hospital of Guangxi University of Traditional Chinese Medicine, Nanning, 530000, People’s Republic of China; 3Affiliated Hospital of Youjiang Medical University for Nationalities, Baise, Guangxi, 533000, People’s Republic of ChinaCorrespondence: Jie Wang, Email yyfywj@126.comObjective: To investigate the mechanism by which resveratrol (Res) ameliorates cognitive impairment (CI) in chronic kidney disease (CKD) rats through modulation of gut microbiota and suppression of inflammation.Methods: A CKD model was established in rats via two intravenous injections of doxorubicin (4 mg/kg, 2 weeks apart). After 8 weeks, renal function and histopathological assessments were performed to confirm the establishment of the CKD model.Rats were divided into control, CKD, and CKD+Res groups. The CKD+Res group received intragastric Res for 6 weeks. Cognitive function was assessed using the Morris water maze. Serum Interleukin-6 (IL-6), Tumor Necrosis Factor-alpha (TNF-α), and Lipopolysaccharide (LPS) levels were measured via ELISA. Histopathology evaluated kidney, colon, and hippocampal damage. Gut microbiota composition was analyzed by 16S rRNA sequencing, and hippocampal Toll-Like Receptor 4 (TLR4)/ the Nuclear Factor-κB (NFκB) pathway proteins were quantified via Western blot.Results: CKD groups exhibited elevated 24-hour urinary albumin, serum urea nitrogen, and creatinine (P < 0.01), with glomerular atrophy. During water maze navigation (days 3– 4), CKD groups showed prolonged escape latency and increased swimming distance versus controls (P < 0.05), which Res intervention alleviated (P < 0.05). In the spatial probe test, CKD rats had fewer platform crossings and shorter target quadrant occupancy (P < 0.01; P < 0.05), both improved by Res (P < 0.05). Hippocampal neuronal damage and elevated serum IL-6, TNF-α, and LPS levels (P < 0.01) were observed in CKD rats, while Res reduced IL-6 and LPS (P < 0.05). Western blot revealed upregulated TLR4/NFκB pathway activation in the CKD group (P < 0.01), suppressed by Res (P < 0.05). Gut microbiota analysis showed increased Gram-negative bacteria in CKD rats and higher Gram-positive bacteria abundance in the Res group. LPS biosynthesis was enhanced in CKD rats (P < 0.05) but attenuated by Res.Keywords: resveratrol, chronic kidney disease, CKD, cognitive impairment, gut microbiota, TLR4/NFκB pathway